The genome and preliminary single-nuclei transcriptome of Lemna minuta reveals mechanisms of invasiveness. Issue 2 (6th December 2021) - Abramson, Bradley W; Novotny, Mark; Hartwick, Nolan T; Colt, Kelly; Aevermann, Brian D; Scheuermann, Richard H; Michael, Todd P
Abstract: The ability to trace every cell in some model organisms has led to the fundamental understanding of development and cellular function. However, in plants the complexity of cell number, organ size, and developmental time makes this a challenge even in the diminutive model plant Arabidopsis ( Arabidopsis thaliana ). Duckweed, basal nongrass aquatic monocots, provide an opportunity to follow every cell of an entire plant due to their small size, reduced body plan, and fast clonal growth habit. Here we present a chromosome-resolved genome for the highly invasive Lesser Duckweed ( Lemna minuta ) and generate a preliminary cell atlas leveraging low cell coverage single-nuclei sequencing. We resolved the 360 megabase genome into 21 chromosomes, revealing a core nonredundant gene set with only the ancient tau whole-genome duplication shared with all monocots, and paralog expansion as a result of tandem duplications related to phytoremediation. Leveraging SMARTseq2 single-nuclei sequencing, which provided higher gene coverage yet lower cell count, we profiled 269 nuclei covering 36.9% (8, 457) of the L. minuta transcriptome. Since molecular validation was not possible in this nonmodel plant, we leveraged gene orthology with model organism single-cell expression datasets, gene ontology, and cell trajectory analysis to define putative cell types. We found that the tissue that we computationally defined as mesophyll expressed high levels of elemental transport genes consistent with this tissue playing a role in L. minuta wastewater detoxification. The L. minuta genome and preliminary cell map provide a paradigm to decipher developmental genes and pathways for an entire plant. Abstract : The genome and single-nuclei transcriptome of the Lesser Duckweed Lemna minuta provide preliminary evidence that tandem gene duplication and tissue-specific expression play roles in invasiveness.